The Islamization of Hijri Calendar-Based Payroll Practices in MSMEs: A Humanities Analysis and Implications for Workers’ Welfare - Siti Andayani; Supriyanto Supriyanto; Budi Susetyo (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study examines the implementation of a Hijri calendar-based payroll system in Micro, Small, and Medium Enterprises (MSMEs) and its implications for workers’ welfare from the perspectives of the Islamization of knowledge and humanities. Using a qualitative case study design, the research was conducted at Rumah Produksi Nopia Estu in Banyumas, Indonesia. Data were collected through in-depth interviews, observation, and documentation, and analyzed using a descriptive-interpretative approach. The findings show that the implementation of the Hijri calendar is not merely an administrative adjustment, but is experienced by workers as a meaningful transformation in payroll practice. Empirically, the system produces both material and non-material effects on workers’ welfare. Materially, employees benefit from a relatively higher payroll frequency over time due to the shorter Hijri lunar cycle, which is perceived as an additional income cycle (“37th salary”). Non-materially, workers report increased feelings of fairness, spiritual well-being, and emotional attachment to work, as the system is understood as aligning economic activity with Islamic values of tawhid and justice. These findings show that the Hijri calendar-based payroll system contributes to a more holistic conception of welfare, integrating economic, social, and spiritual dimensions. Therefore, it may serve as an alternative model for Islamic-oriented payroll management in MSMEs that emphasizes both material improvement and value-based well-being